PEMBELAJARAN INKUIRI MODEL ALBERTA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP - Muhamad Rizal Usman (Delta-Pi: Jurnal Matematika dan Pendidikan Matematika, 2014)
This research is motivated by the results of previous studies which showed that the mathematical creative thinking abilities of students are still not as expected. This study focuses on the effort to determine the increase in mathematical creative thinking abilities of students as a result of the inquiry learning model of Alberta. This study is an experimental study with the entire population of one junior high school students in the city. Samples were students of class VII school. The study sample as many as 73 students, 36 students in grade 37 student experiments and the control class. Based on the analysis of data obtained conclusions: (1) achievement of creative thinking ability of students receiving mathematical model of inquiry learning Alberta better than students who received conventional learning. (2) Improving creative thinking abilities of students receiving mathematical model of inquiry learning Alberta better than students who received conventional learning. (3) there are differences in improvement of mathematical creative thinking abilities by category KAM.